2020
DOI: 10.1155/2020/6623830
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Efficacy of a Novel Antibiotic-Eluting Injectable Platelet-Rich Fibrin Scaffold against a Dual-Species Biofilm in an Infected Immature Root Canal Model

Abstract: Background and Aims. This study was aimed at evaluating the antibacterial property of an injectable platelet-rich fibrin (I-PRF) scaffold containing triple antibiotic mixture against an Actinomyces naeslundii (A. naeslundii) and Enterococcus faecalis (E. faecalis) biofilm in an infected immature root canal model. Methods. A dual-species biofilm was inoculated inside the root canals via a series of centrifugal cycles. The samples were allocated to three experimental groups (i.e., G1: triple antibiotic mixture, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Possible scenarios for implementation of a MIREP concept as well as a suggested clinical protocol are provided in Figures 1 , 2 according to the clinical need of each respective case; for example whether the infection is a long-standing one or not and whether a single visit or multiple visits regimen is recommended, there can be several proposed regenerative strategies. The nature/source of the scaffold to be placed could have immunomodulatory function ( Khung et al, 2015 ; Shen et al, 2020 ), antibacterial action with controlled antibiotic release ( Moon et al, 2018 ) or a biologically inspired scaffold with dual action ( Hussey et al, 2019 ; Rafiee et al, 2020 ). One suggested single visit-MIREP protocol for a traumatized permanent maxillary necrotic tooth ( Figure 2 ) proposes a contracted endodontic cavity design followed by minimally tapered canal preparation and a disinfection regimen including combined NBW with 1.5% NaOCl followed by the placement of ECM-based hydrogel with/without cell-specific exosomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible scenarios for implementation of a MIREP concept as well as a suggested clinical protocol are provided in Figures 1 , 2 according to the clinical need of each respective case; for example whether the infection is a long-standing one or not and whether a single visit or multiple visits regimen is recommended, there can be several proposed regenerative strategies. The nature/source of the scaffold to be placed could have immunomodulatory function ( Khung et al, 2015 ; Shen et al, 2020 ), antibacterial action with controlled antibiotic release ( Moon et al, 2018 ) or a biologically inspired scaffold with dual action ( Hussey et al, 2019 ; Rafiee et al, 2020 ). One suggested single visit-MIREP protocol for a traumatized permanent maxillary necrotic tooth ( Figure 2 ) proposes a contracted endodontic cavity design followed by minimally tapered canal preparation and a disinfection regimen including combined NBW with 1.5% NaOCl followed by the placement of ECM-based hydrogel with/without cell-specific exosomes.…”
Section: Discussionmentioning
confidence: 99%
“…An antibiotic-releasing injectable Platelet-Rich-Fibrin (I-PRF) scaffold was tested against a dual-species biofilm colonized inside the root canal, showing significant reduction in the bacterial count. The engineered biocompatible autologous scaffold that contained both antibiotics and growth factors, could favor regeneration rather than repair ( Rafiee et al, 2020 ). Moreover, THP-1 macrophages were seeded on a concentrated growth factors (CGF) scaffold, revealing the immunoregulatory role of CGF in macrophage functional activities.…”
Section: Alternative “Biomimetic” Strategies Could Decrease Cytotoxic...mentioning
confidence: 99%
“…29 Finally, an additional four studies found that i-PRF demonstrated antimicrobial efficacy against both periodontal and cariogenic pathogens. [30][31][32][33]…”
Section: Us E Of I-prf For Improved Wound He Aling In the Or Al C Avit Ymentioning
confidence: 99%
“…It was found that delivering a triple antibiotic mixture using i-PRF was most efficient at reducing bacterial loads when compared to other delivery methods. 31 Although these studies remain limited…”
Section: Clini C Al Us E Of I-prf In Endodontic Smentioning
confidence: 99%
“…This liquid blood derivative is enriched with high concentrations of platelets, leukocytes, and growth factors [ 31 33 ]. Recent studies have reported that i-PRF provides a three-dimensional fibrin-dynamic gel embedded with platelets, leukocytes, type-I collagen, osteocalcin, and growth factors [ 31 ] with the potential to modulate inflammatory processes [ 34 ], exert anti-bacterium and anti-biofilm activities [ 35 , 36 ], and promote osteogenesis [ 37 39 ]. Compared to PRF, i-PRF results in better bone regeneration [ 39 ], treatment of gingival recession defects [ 40 ], and elimination of endodontic infection [ 36 ].…”
Section: Introductionmentioning
confidence: 99%